Development Of Childrens Ability To Put Words Togather In Sentence - Fadhila; Sirrul Aulia; Miftahul Jannah; Bima Bahari (Philosophiamundi, 2023)
The purpose of this study was to examine the development of the utterance hypothesis, which is the observation of children's ability to construct their first words, based on the psychometric values ??of a new sentence interpretation task developed for this purpose.It's about examining developmental changes. To determine the method in this article, we use a library research approach, including a survey asking people around how long it takes for a child to learn to form words orally. I used Between the ages of 6 and 11, children begin speaking and arranging words by hearing two structures, one in canonical word order and two in nonconical word order. After each sentence, children selected the picture of the word that they thought "performed the action" as quickly as possible. Children interpreted sentences containing standard imperatives more accurately and quickly than sentences containing nonstandard imperatives. Older children (ADEM =10: 8) were more accurate and faster than younger children (ADEM=8: 1) in all tenses. Older and younger children showed similar patterns of errors across sentence types. Also, this task has high validity and reliability, making it suitable for learning with children.